Low complexity interference compensation for DFRFT‐based OFDM system with CFO. Issue 14 (1st August 2020) - Trivedi, Vinay Kumar; Kumar, Preetam
Abstract : Discrete fractional Fourier transform (DFRFT) based orthogonal frequency division multiplexing (OFDM) system significantly outperforms the conventional discrete Fourier transform (DFT) based OFDM system in the presence of carrier frequency offset (CFO). However, to achieve the interference‐free performance, the residual interference remaining after the channel equalisation in the fractional Fourier domain needs to be compensated. To enable this residual interference compensation with low complexity after DFRFT at the receiver, an accurate and generalized expression for inter‐carrier interference (ICI) coefficient from interfering to the desired subcarrier is derived over a multipath fading channel with CFO. The derived ICI coefficient is validated at the DFRFT angle equal to π / 2 (i.e., for DFT‐OFDM system) and over AWGN and flat channel. Monte Carlo simulation of symbol error rate (SER) over the Rayleigh fading channel is also carried out to verify the derived theoretical closed‐form ICI coefficient for different values of the DFRFT angle. At the receiver, a low complexity residual interference cancellation stage is introduced by utilizing the banded matrix implementation of the derived closed‐form residual ICI matrix for the DFRFT‐OFDM system which only needs to perform O ( N ) operations for closely preserving the interference‐free performance.